PROSPECTS FOR THE INTRODUCTION OF CABLE CAR TRANSPORT (Transport systems and technologies, 2023)
Objective. The main purpose of this article is to review and analyze the possibilities of integrating cableway transport into the urban environment for unloading and redistribution of passenger flows in large cities, taking into account current issues of energy efficiency and resource conservation. Methods. It is determined that the successful functioning of the state depends on the transport process. At the same time, road transportation is becoming increasingly important. Statistical data for 2020 and 2021 on freight and passenger transportation were used. Statistics on road accidents have been increasing in recent years. The issues of passenger and freight safety are relevant. When designing a modern alternative mode of transport, it is important to consider possible innovative solutions. One of such approaches is the position on energy efficiency and resource conservation. At the same time, energy efficiency concerns not only the engineering processes of these transport systems, but also the operation of cable cars. An innovative solution can be rope systems in which cabins move along the carrier rope and are equipped with their own drive. Results. The main functions and significance of the transport system of the country, the main modes of transport, including passenger, are considered. The transport problem of large cities due to congestion of roads is determined. A review and analysis of the possibilities of integrating ropeway transport into the urban environment for unloading and redistribution of passenger flows in large cities, taking into account current issues of energy efficiency and resource conservation. The prospects for the introduction of cable transport are considered. Scientific novelty. The problems of transport of Ukraine are determined. Statistical data on road accidents, volumes of freight and passenger traffic are used. The proposed solution to unload the roads of large cities, in order to improve the safety of passenger traffic and environmental friendliness in transport. The scheme of self-propelled cable car with individual drive is developed. Practical significance. The issue of energy efficiency concerns the rational use of energy resources, which means that the use of less energy resources will reduce the cost of transportation. The use of energy efficient technologies will allow less detrimental impact on the environment, which is of great importance in a large city.
Keywords: passenger transportation; cable car; cable transport; energy efficiency; self-propelled cars; alternative transport.